2019
DOI: 10.1108/ijefm-07-2018-0046
|View full text |Cite
|
Sign up to set email alerts
|

Strategic leveraging: evidences of small-scale sport events

Abstract: Purpose The purpose of this paper is to identify the strategic leveraging goals associated with a portfolio of small-scale events and to analyze their implementation process (actors/tactics: who did what?) in order to propose new leverage typologies through new empirical research evidence. Design/methodology/approach Three techniques of data collection conducted the fieldwork: qualitative interviewing, direct observation and documental research. Based on the principles of grounded theory and using qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 64 publications
0
13
0
Order By: Relevance
“…Findings pinpointed the lack of a comprehensive deliberate vision to systematically cultivate synergies among events and to foster their supplemental interrelations, which limited cumulative benefits (Pereira et al , 2015). In extending this study, Pereira et al (2020) found the coexistence of multiple leveraging goals and a subsequent set of tactics to be effectively executed via the coordination of the network of event-supporting organizations, including both local and external actors. This corroborates previous claims (Ziakas, 2014a, 2014b, 2019) for the critical part of an exogenous to event organizers board tasked with the coordination of portfolio leveraging actions.…”
Section: Event Leveraging: Theoretical Underpinnings Of the Event Portfolio Outlookmentioning
confidence: 74%
See 2 more Smart Citations
“…Findings pinpointed the lack of a comprehensive deliberate vision to systematically cultivate synergies among events and to foster their supplemental interrelations, which limited cumulative benefits (Pereira et al , 2015). In extending this study, Pereira et al (2020) found the coexistence of multiple leveraging goals and a subsequent set of tactics to be effectively executed via the coordination of the network of event-supporting organizations, including both local and external actors. This corroborates previous claims (Ziakas, 2014a, 2014b, 2019) for the critical part of an exogenous to event organizers board tasked with the coordination of portfolio leveraging actions.…”
Section: Event Leveraging: Theoretical Underpinnings Of the Event Portfolio Outlookmentioning
confidence: 74%
“…Going back to the roots of portfolio thinking, Pereira et al (2015, 2020) scrutinized the strategic leveraging processes of a sport event portfolio in the Portuguese tourist resort Portimão that put together a specialized portfolio of coastal events to enhance its nautical brand. Findings pinpointed the lack of a comprehensive deliberate vision to systematically cultivate synergies among events and to foster their supplemental interrelations, which limited cumulative benefits (Pereira et al , 2015).…”
Section: Event Leveraging: Theoretical Underpinnings Of the Event Portfolio Outlookmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the role of sport events in tourism planning, place marketing and portfolios has been explored primarily through the lens of sport event leveraging ( Chalip, 2004 ; Kelly & Fairley, 2018 ; Pereira, Mascarenhas, Flores, & Pires, 2015 ; Pereira, Mascarenhas, Flores, Chalip, & Pires, 2020 ; Taks, Chalip, Green, Kesenne, & Martyn, 2009 ; Ziakas, 2014b ), co-branding ( Chalip & Costa, 2005 ; Jago, Chalip, Brown, Mules, & Ali, 2003 ; Westerbeek & Linley, 2012 ), sport and cultural tourism ( Boukas, Ziakas, & Boustras, 2012 , 2013 ; Buning, Cole, & McNamee, 2016 ; Gibson, Kaplanidou, & Kang, 2012 ; Ziakas & Boukas, 2012 , 2016 ), and their contribution to urban development, place attractiveness and residents’ quality of life ( Clark & Misener, 2015 ; Dragin-Jensen, Schnittka, & Arkil, 2016 ; Ziakas & Costa, 2011b ). Interestingly, notwithstanding the overlap between sport events and tourism, this line of research is not fully integrated with the core tourism literature on event portfolios ( Ziakas, 2020 ).…”
Section: Other Theories and Themes Of Relevance In The Tourism Literamentioning
confidence: 99%
“… International Journal of Event and Festival Management Empirical Journal Article Indicates the role of a small-city event portfolio in enhancing quality of life for families and maintaining indigenous cultures. Pereira, E., Mascarenhas, M., Flores, A., Chalip, L., & Pires, G. (2020) . Strategic leveraging: Evidences of small-scale sport events.…”
Section: Synopsis and Conclusionmentioning
confidence: 99%